2018
DOI: 10.1080/10942912.2018.1534124
|View full text |Cite
|
Sign up to set email alerts
|

Model for the prediction of potato impact damage depth

Abstract: A model was developed to predict the impact damage depth of potato. The model consisted of a series of differential equations derived from the force equilibrium on a differential element, which, respectively, governs the relationships among the potato collision displacement and initial collision speed, natural angular frequency of undamped system, and damping ratio. For the collision displacement of potato impact with the rod, the study used the impact test rig and acceleration acquisition system to measure th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 15 publications
2
13
0
Order By: Relevance
“…These were manually obtained from crop planting base of Inner Mongolia Agricultural University. Subsequently, the samples were washed in cold water and then sorted into four groups based on the masses of 150 ± 5 g, 250 ± 5 g, 350 ± 5 g, and 450 ± 5 g. Finally, all of potatoes were stored at the fridge and to produce potato samples at 5 C, 15 C, and 23 C (Xie et al, 2018).…”
Section: Raw Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…These were manually obtained from crop planting base of Inner Mongolia Agricultural University. Subsequently, the samples were washed in cold water and then sorted into four groups based on the masses of 150 ± 5 g, 250 ± 5 g, 350 ± 5 g, and 450 ± 5 g. Finally, all of potatoes were stored at the fridge and to produce potato samples at 5 C, 15 C, and 23 C (Xie et al, 2018).…”
Section: Raw Materialsmentioning
confidence: 99%
“…Usually, these adopted experimental instruments included pendulum collision device, free drop collision device, electronic potato, instrumented sphere and acceleration measuring unit (Canneyt, Tijskens, Ramon, Verschoore, & Sonck, 2004;D anil a, 2015;D anil a & Gaceu, 2010;Geyer et al, 2009;Guo, Wang, Li, Chen, & Li, 2016;Hyde, Brown, Timm, & Zhang, 1992;Mathew & Hyde, 1997;Molema, Verwijs, Berg, & Breteler, 1997;Nikara, Ahmadi, & Nia, 2018;Rady & Soliman, 2015;Strehmel et al, 2010). At the same time, various influence factors on potato impact damage also were published, which mainly consisted of specific tuber properties (tuber mass, potato variety, tuber shape, specific gravity), collision states(drop height, impact material, impact number, impact angle), storage conditions such as temperature and cultivation conditions (Baritelle & Hyde, 2003;Ito, Sakai, Hata, & Takai, 1994;Johnston & Wilson, 1969;Koch, Naumann, & Pawelzik, 2019;Mathew & Hyde, 1997;Molema et al, 1997;Xie, Wang, & Deng, 2018). As for the main indexes of impact evaluation, it generally contained collision pressure, impact acceleration, injury criterion (damage volume and depth), and respiratory rate (Baritelle & Hyde, 2003;D anil a, 2015;D anil a & Gaceu, 2010;Geyer et al, 2009;Mathew & Hyde, 1997;Molema et al, 1997;Rady & Soliman, 2015).…”
mentioning
confidence: 99%
“…Impact damage to potatoes is a common phenomenon during harvesting and post-harvesting operations. [1][2][3] It has been reported that 70% of the damage to potatoes is caused by harvesting, and impact and pressure are the main causes. [4] Mechanical damage and collision abrasion seriously affect potato yield and cause a dual decline of potato appearance and quality that affect the development of the entire potato industry.…”
Section: Introductionmentioning
confidence: 99%
“…In the field of experimental research, some researchers have used pendulum devices to study potato impact problems. Xie [1] established a potato impact damage depth model using a single pendulum impact device and found the order of influencing factors that affect the impact damage depth through orthogonal experiments. Some researchers used a pendulum impact device to study the potato impact response with different tuber temperatures, initial heights, and impact materials and described the equation of the shape and volume of the bruise spots.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation